Early Schoolers’ Social Competence: An Exploration - Sattar, Amira; Farooq, Muhammad Shahid (JECCE, 2024)
The present study endeavors to measure the social competence of early schooler by documenting the perceptions of teachers. Social competence is an indispensable factor concerning the students’ internal ability that predicts their actual learning outcome gained from different social perspectives consciously and unconsciously coming from various societal formal and informal institutions; such as schools, madrassas, masajid, or social gatherings, and from their peers’ interaction. The design of this study was descriptive in its nature using a questionnaire consisting of 52 items. The instrument was further divided into 12 factors. Each factor is intended to measure preschool students’ social competence by taking their teachers’ perceptions. Data were collected from one district of Punjab to measure the social competence of early preschooler explicitly. The number of sample teachers was 120 from 40 preschools selected by using a simple random sampling technique to collect the data. From the main finding of the study, the factor ‘patriotism’ and ‘showing respect to the public’ are found to be extensively believed and practiced by early learners. The study emphasized regular activities to be practiced by preschool teachers to enhance the social competence of students.